A PRELIMINARY RESERVOIR SIMULATION STUDY ON CO2 FLOOD IN MERUAP FIELD, SOUTH SUMATRA, INDONESIA - Yonathan Loana, Andrew
This paper presents the results of a feasibility study aimed at extending the production life of an oilfield in Indonesia through EOR (Enhanced Oil Recovery) employing the carbon dioxide (CO2) injection technique This research used a modeling approach to optimize the CO2 flood by improving the oil sweep efficiency of CO2 floods. A full compositional simulation model using a detailed geologic characterization was built to optimize the injection design. The model is a quarter of a five-spot injection pattern and covers 281 acres in Meruap Field. The Peng-Robinson equation of state (EOS) was chosen to describe the phase behavior during the CO2 flooding. Several sensitivity runs were made to improve the CO2 sweep efficiency and increase the oil recovery. This study found that the optimum CO2 injection rate for Meruap formation is approximately 6000 res bbl (33687.5 scf/D) of carbon dioxide. Simulation results also indicate that a water-alternating-gas (WAG) ratio of 2:1 along with an ultimate CO2 slug of 100% hydrocarbon pore volume (HCPV) will allow the oil recovery to achieved 44.7% at miscible injection process and 27% at immiscible injection process.